2013
DOI: 10.9789/2175-5361.2013v5n2p3677
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of People in Cardiac Surgeries: A Descriptive Study

Abstract: Objective: To characterize patients undergoing cardiac surgery at a referral hospital in northern of Ceara. Method: This is a quantitative and descriptive study using documentary analysis carried out by 176 medical records in accordance with the ethical aspects of Resolution 196/96. Results: We identified predominantly men, married, living in distant cities of the health service and a greater tendency for people over 40 years old. The hospital stay was low, contributing to reduction of risks related to hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Outras investigações trazem a média de tempo de internação para CRM entre três e 11 dias e associam a baixa permanência hospitalar à redução de complicações e riscos relacionados à internação (11)(12) , influenciando inclusive a disponibilidades de leitos (11) .…”
Section: Discussionunclassified
“…Outras investigações trazem a média de tempo de internação para CRM entre três e 11 dias e associam a baixa permanência hospitalar à redução de complicações e riscos relacionados à internação (11)(12) , influenciando inclusive a disponibilidades de leitos (11) .…”
Section: Discussionunclassified
“…This can be explained by the increase in the Brazilian elderly population, and consequently, an increase in labor market participation. 15 It has been shown that the most found risk factors or previous diseases were HBP (n=82; 79.61%), DM (n=37; 35.92%), and CAD (n=21; 20.38%). Similar data were found through a study on the epidemiological profile of myocardial revascularization surgeries in 2011, which showed a prevalence of HBP (88.3%), followed by CAD (50.4%), and DM (32.9%).…”
Section: Sd = Standard Deviation; Se = Standard Errormentioning
confidence: 98%